Ethological Evaluation of the Effects of Social Defeat Stress in Mice: Beyond the Social Interaction Ratio - Henriques-Alves, Aron M.; Queiroz, Claudio M. (Frontiers in Behavioral Neuroscience, 2016)
In rodents, repeated exposure to unavoidable aggression followed by sustained sensory treat can lead to prolonged social aversion. The chronic social defeat stress model explores that phenomenon and it has been used as an animal model for human depression. However, some authors have questioned whether confounding effects may arise as the model also boosts anxiety-related behaviors. Despite its wide acceptance, most studies extract limited information from the behavior of the defeated animal. Often, the normalized occupancy around the social stimulus, the interaction zone, is taken as an index of depression. We hypothesized that this parameter is insufficient to fully characterize the behavioral consequences of this form of stress. Using an ethological approach, we showed that repeated social defeat delayed the expression of social investigation in long (10 min) sessions of social interaction. Also, the incidence of defensive behaviors, including stretched-attend posture and high speed retreats, was significantly higher in defeated mice in comparison to controls. Interestingly, a subpopulation of defeated mice showed recurrent and non-habituating stretched-attend posture and persistent flights during the entire session. Two indexes were created based on defensive behaviors to show that only recurrent flights correlates with sucrose intake. Together, the present study corroborates the idea that this model of social stress can precipitate a myriad of behaviors not readily disentangled. We propose that long sessions (>150 s) and detailed ethological evaluation during social interaction tests are necessary to provide enough information to correctly classify defeated animals in terms of resilience and susceptibility to social defeat stress.